Performing Arts As A Medium For Social Integration Of Migrant With Local Community: Lesson From Indonesia - Tutung Nurdiyana; Muhammad Najamudin (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2022)
The migrants in Barito Kuala Regency developed the art of dance originating from their area. However, the art performances they show are one of the reinforcements for their social integration with the local community. This paper aims to: (1) describe the reasons for the migrants to develop their performing arts. (2) analyzing the role of performing arts as a medium for social integration of migrants with local communities. This research uses qualitative research methods and has been carried out in Sidomulyo Village and Dandan Jaya Village, Barito Kuala Regency, South Kalimantan Province. 10 Informants were interviewed. Data was carried out by observation, in-depth interviews, and diaries and was analyzed by ethnographic analysis. This study found that (1) the reason of migrants to develop art is to always remember their original identity. (2) Art becomes a medium for social integration through (a) adapting the art of the migrant community to the art of the local community (b) Performing arts As a means of public entertainment (c) social interactions that are developed among all residents during performing arts performances. Based on the research findings, this study suggests strengthening arts that adapt local arts to strengthen social integration, especially in multi-ethnic communities.